Protocol for Birmingham Atrial Fibrillation Treatment of the Aged study (BAFTA): a randomised controlled trial of warfarin versus aspirin for stroke prevention in the management of atrial fibrillation in an elderly primary care population [ISRCTN89345269] - Mant, J; Richards, S; Hobbs, F; Fitzmaurice, D; Lip, G; Murray, E; Banting, M; Fletcher, K; Rahman, J; Allan, T; Raftery, J; Bryan, S (BioMed Central, 2003)
Background: Atrial fibrillation (AF) is an important independent risk factor for stroke. Randomised controlled trials have shown that this risk can be reduced substantially by treatment with warfarin or more modestly by treatment with aspirin. Existing trial data for the effectiveness of warfarin are drawn largely from studies in selected secondary care populations that under-represent the elderly. The Birmingham Atrial Fibrillation Treatment of the Aged (BAFTA) study will provide evidence of the risks and benefits of warfarin versus aspirin for the prevention of stroke for older people with AF in a primary care setting. Study design: A randomised controlled trial where older patients with AF are randomised to receive adjusted dose warfarin or aspirin. Patients will be followed up at three months post-randomisation, then at six monthly intervals there after for an average of three years by their general practitioner. Patients will also receive an annual health questionnaire. 1240 patients will be recruited from over 200 practices in England. Patients must be aged 75 years or over and have AF. Patients will be excluded if they have a history of any of the following conditions: rheumatic heart disease; major non-traumatic haemorrhage; intra-cranial haemorrhage; oesophageal varices; active endoscopically proven peptic ulcer disease; allergic hypersensitivity to warfarin or aspirin; or terminal illness. Patients will also be excluded if the GP considers that there are clinical reasons to treat a patient with warfarin in preference to aspirin (or vice versa). The primary end-point is fatal or non-fatal disabling stroke (ischaemic or haemorrhagic) or significant arterial embolism. Secondary outcomes include major extra-cranial haemorrhage, death (all cause, vascular), hospital admissions (all cause, vascular), cognition, quality of life, disability and compliance with study medication.